P32 The clinical and financial burden to the nhs of patients with certain underlying comorbidities that develop hospitalised pneumonia. (December 2018) - Jones, D; Campling, JA; Chalmers, JD; Vyse, A; Madhava, H; Slack, M
Abstract : Background: The clinical and economic costs of an episode of hospitalised pneumonia are usually assumed to be short-lived with patients subsequently returning to their previous health-state. We hypothesised that a diagnosis of hospitalised pneumonia in an individual within a specific risk group would have clinical and economic implications that would go beyond the initial episode. Aim: Determine, within the NHS context, the clinical and financial burden of hospitalised pneumonia in 6 risk groups over a 4 year period utilising the Hospital Episodes Statistics (HES) database, which incorporates the entire population of England that visit a hospital. Method: We retrospectively analysed HES data on individuals≥18 years. Those with a specified risk group diagnosis were tracked from 2012 to 2015. Individuals developing hospitalised pneumonia in the year following their risk group diagnosis were matched through propensity scoring to an individual within that risk group who did not go on to develop hospitalised pneumonia. Hospital activity, costs and mortality were compared between the two groups over the next 3 years. Results: Conclusion: This study utilises an entire adult population to ascertain the impact of hospitalised pneumonia in patients with certain underlying comorbidities. Hospitalised pneumonia has a significant long term impact on those within specific risk groups, resulting in additional hospital admissions and associated costs, and the initial pneumonia episode appears to significantly increase the likelihood of mortality.